Divergent reactivity of phosphapalladacycles toward E-H (E = N, P, As) bonds - Tay, Wee Shan (2022)
Secondary arsines were observed to decomplex strongly chelating phosphapalladacycles rapidly under mild conditions. As-H bond migration led to ortho-protonation of the C,P ligand. On the other hand, N-H and P-H bonds in amine and phosphine analogues were acidified under the same conditions and no ligand decomplexation of the metallacycle was observed. Subsequently, secondary arsines bearing the As-H bond were applied in deuteration by directed ortho-metalation (DoM) and decomplexation strategies. In the former, HAsPh2 was a convenient deuterium shuttle which facilitated the ortho-deuteration of DoM-palladacycle intermediates under neutral conditions. High deuterium incorporation (>99%) was achieved without specialized preformed deuterating agents. In the latter, HAsPh2 afforded the preligands of monomeric, dimeric, bidentate, and tridentate complexes of Pd in excellent yields of 95-98% within 30 min at room temperature. Key reaction steps for the intramolecular insertion of As-H into the Pd-C bond were outlined, and the effects of regioisomerism on the ortho-protonation pathway were evaluated.